A Phonological Analysis of Closure and Consonant Duration of English and Pashto Stop Sounds - Khan, Bilal; Shah, Said Arfan Ali; Aman, Saba (Annals of Human and Social Sciences, 2024)
The main objectives of the study is to investigating the acoustic properties of English and Pashto Stops. It investigates the L1 Pashto effect on the acquisition of English Stops and to find out whether the acquisition process of Pashto learners agrees to the speech learning model of Flege (1987). The data analyzed in the study has been collected through microphone and Laptop in the shape of recordings from the educated and uneducated two groups of Pashto speakers. The data is analyzed using the Praat software. The analysis focuses on the closure and complete consonant duration of stops. It proves that there are certain similarities and differences in the acoustics properties of English and Pashto stops. Moreover, it proves that the results partially agree to the speech learning model. The study recommends further research work on Pashto language in general and on the acoustic analysis of the Pashto language in particular.